Bibliography on Cold Regions Science and Technology. Volume XXVII. Part 2. - COLD REGIONS RESEARCH AND ENGINEERING LAB HANOVER N H (1973)
The report, part two of a two part series, contains the author and subject indexes. See also Part 1, AD-768 099.